(untitled) (Journal of the Management Sciences, 2024)
The challenging environmental dynamics, had contributed considerably to identification of human capacity utilization (person-post fit) relevance in the assessment of organization performance. This study explores Human Capacity Utilization and Performance of Micro Finance Banks across the three senatorial constituencies, of Kwara State. Using descriptive and a cross sectional survey, population of study made up of 36 Microfinance Banks, purposely selected with not less than five (5) years operational existence from the three (3) divisions of Kwara State. Staffs focus comprising of management staff, administrative and technical staff. The sample size is 108 respondents, on an average of three (3) persons from .a Microfinance Banks gotten from Researchers’ Advisers Table. Simple Random Sampling was adopted to administer the copies of 5- options Likert Scale Questionnaire to collect data; Multiple Regression was used to test the hypotheses. Findings shows that, from hypothesis one and two, alternate hypothesis was accepted which states that there is significant effect of knowledge accessibility on organizational efficiency, and that, there is significant influence of workforce optimization on organizational profitability. The study concludes that microfinance banks need improve their services delivery as staffs are not fully trained, thus limiting competencies and competitiveness ability needed to meet the bank’s target. The study recommends that the need to remain afloat and relevant to purpose of doing business requires strong capacity development support and knowledge of innovation ideas just like the new generational banks; hence the Nigerian Microfinance banks need to have a well-defined organizational job structure, bank job responsibilities to enhance human resource utilization.